2016
DOI: 10.3399/bjgp16x683413
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of suicide bereavement: a qualitative study exploring the role of the GP

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 18 publications
4
26
0
1
Order By: Relevance
“…Importantly, consistent with other qualitative analyses of adolescent mothers' experiences (Arenson, 1994;Seamark & Lings, 2004), all the mothers we interviewed were motivated to parent better than they perceived their own mothers had. However, mothers differed in their definitions of what being a good mother meant.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Importantly, consistent with other qualitative analyses of adolescent mothers' experiences (Arenson, 1994;Seamark & Lings, 2004), all the mothers we interviewed were motivated to parent better than they perceived their own mothers had. However, mothers differed in their definitions of what being a good mother meant.…”
Section: Discussionsupporting
confidence: 85%
“…However, Barratt, Roach, Morgan, and Colbert (1996) found that adolescent mothers reported higher well-being postpartum than their same-aged peers without children. Adolescent childbearing may be protective for drug use and binge drinking (Fletcher, 2012), may serve as a catalyst for lifestyle changes, and may also be associated with higher self-esteem and sense of identity (Breen, 2014;Hanna, 2001;Larkins et al, 2011;Mulherin & Johnstone, 2015;Seamark & Lings, 2004;Shea, Bryant, & Wendt, 2015;Sheeran, Jones, & Rowe, 2016;Smith-Battle & Leonard, 1998). In short, compared with alternative options, the sense of life meaning and direction associated with becoming an adolescent mother may be a protective factor for women from disadvantaged backgrounds (Arai, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…by a relative's suicide. [17][18][19] These studies highlight the importance of services being informed by the experiences of suicidebereaved people. However, parents are potentially one of the most traumatised groups of suicide-bereaved people, and there is less evidence available [20][21][22] about how to support them in the UK.…”
Section: Resultsmentioning
confidence: 98%
“…The GP will often be an initial source of support for those bereaved by suicide, and GPs have previously been recognised as key in the provision of care to this group. 18 In a review of the literature, the evidence base for GP services to inform their support of people bereaved by suicide was considered limited but GPs viewed bereavement care as an important part of their role. 23 The review also found that there was a great deal of variability among GP services in terms of the protocols they had in place to support those bereaved by suicide: some had clear structures in place but others did not.…”
Section: Resultsmentioning
confidence: 99%
“…This study showed that GPs were particularly helpful when they acknowledged the loss and lived life of the deceased, helped to reduce stigma, and directly supported families during the grief journey. 6 Finally, GPs in all European countries may take note of the study by Verweij and colleagues from the Netherlands that shows that mindfulness training significantly reduces emotional exhaustion in GPs who are suffering from burnout. 7 Collectively, these studies affirm the central role of primary care in addressing the mental health challenge at all stages of life.…”
mentioning
confidence: 99%